Chronic nicotine toxicity is prevented by aqueous garlic extract - (:unkn) unknown (SPRINGER, 2005)
Based on the potent antioxidant effects of garlic, we investigated the putative protective role of aqueous garlic extract (AGE) against nicotine-induced oxidative organ damage. Male Wistar albino rats (200-250 g) were injected with nicotine hydrogen bitartrate (0.6 mg/kg; i.p.) alone or with aqueous garlic extract (125 mg/kg; i.p.) for 21 days. At the end of the experimental period (22(nd) day) rats were killed by decapitation. The aorta, heart, kidney and urinary bladder tissues were taken for the determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen contents. Blood urea nitrogen (BUN) and creatinine concentrations and lactate dehydrogenase (LDH) levels in blood were measured for the evaluation of renal functions and tissue damage, respectively. Tissues were also examined microscopically. The decrease in GSH levels and increases in MDA level, MPO activity and collagen contents induced by chronic nicotine administration indicated that tissue injury involves free radical formation. Treatment of rats with AGE restored the reduced GSH levels while it decreased MDA levels as well as MPO activity. Increased collagen contents of the tissues by chronic nicotine were reversed back to the control levels with AGE. Since AGE administration reversed these oxidant responses, improved renal function and histological damage, it seems likely that AGE protects the tissues against nicotine-induced oxidative damage.
Keywords: aqueous garlic extract; nicotine; oxidative damage; VASCULAR ENDOTHELIAL-CELLS; ALLYL CYSTEINE SULFOXIDE; LIPID-PEROXIDATION; RATS; DAMAGE; GLUTATHIONE; MELATONIN; OXYGEN; MYELOPEROXIDASE; CONSTITUENTS